Optimizing the Madrasah Research Program through Proposal Writing Training and Exploration of Research Trends in the Madrasah Young Researchers Supercamp - Suratman, Suratman; Hamid, Nur (Pascasarjana Universitas Mataram, 2025)
The National Madrasah Research Program serves as a powerful platform for madrasah students to compete at both national and international levels in scientific research through the Madrasah Young Researchers Supercamp (MYRES). This program aims to foster outstanding young talents with extraordinary creative ideas through scientific writing competitions. However, challenges persist, such as limited research skills among teachers, a lack of research-oriented guidebooks, and minimal training and mentoring for madrasah teachers. Students also show low interest in understanding the structure of scientific writing, and their research skills are generally considered underdeveloped. This study aims to optimize the Madrasah Research Program by providing training in proposal writing and exploring current research trends. The method used is Participatory Action Research (PAR), which includes the stages: to know, to understand, to plan, to act, and to change. The participants targeted in this study are mentor teachers and students. Based on the results, the training for teachers and students successfully enhanced the effectiveness of the Madrasah Research Program, particularly through workshops and mentoring in writing scientific articles. This improvement was reflected in several areas: increased potential in scientific writing, better understanding of managing the Madrasah Research Program, a greater number of written proposals, and higher interest and comprehension among participants regarding scientific work. Furthermore, participants demonstrated a stronger commitment to producing quality scientific writing, as evidenced by the availability of research idea documents developed into proposals aligned with the MYRES competition framework.